DEVELOPMENT OF MELATIK: INTERACTIVE LEARNING MULTIMEDIA TO ENHANCE STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN INFORMATICS EDUCATION - Syamsudin, Enang; Rahmadonna, Sisca (Universitas Indraprasta PGRI, 2025)
This research aims to (1) develop ICT learning multimedia for class X Senior High School/Madrasah Aliyah students, (2) assess its feasibility and practicality, and (3) examine its effectiveness in enhancing students' motivation and learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and the MDLC approach (Multimedia Development Life Cycle). The research was conducted at Madrasah Aliyah Ma'arif Cilacap Tengah, involving class X-1 as the experimental group and class X-2 as the control group. Data collection methods included interviews, observations, questionnaires, and learning outcome tests, analyzed using qualitative and quantitative descriptive techniques. The results showed that: (1) ICT learning multimedia is highly feasible based on media expert validation (3.72,